SIMULASI ALIRAN TRANSONIK DUA DIMENSI BERDASARKAN PERSAMAAN NAVIER-STOKES DENGAN JARINGAN KISI SEGITIGA DAN SEGIEMPAT - Syahlan , Arief
Abstrak Two-dimensional Navier-Stokes equations are solved to simulate the two-dimensional viscous transonic flows. Solution is achieved numerically using finite volume approach for solving space discretization and Runge-Kutta scheme for solving time integration. The unknown variables are stored at the cell vertices. Reynolds averaged Navier-Stokes equations are solving in order that turbulence flows can be simulated. Algebraic turbulence model by Baldwin-Lomax is used as closure in Reynolds averaged equations. Numerical simulation is performed using triangular and quadrilateral grid. Quadrilateral grid is generated using algebraic method and conformal mapping method., mean while triangular grid is generated using Delaunay triangulation from those two methods above. Calculation of pressure coefficient (Cp) distribution for inviscid flows is compared to MSES code, mean while calculation for viscous flows is compared to wind tunnel experiment results.